Activatable Small‐Molecule Photoacoustic Probes that Cross the Blood–Brain Barrier for Visualization of Copper(II) in Mice with Alzheimer's Disease. Issue 36 (1st August 2019) - Wang, Shichao; Sheng, Zonghai; Yang, Zhenguo; Hu, Dehong; Long, Xiaojing; Feng, Gang; Liu, Yubin; Yuan, Zhen; Zhang, Jingjing; Zheng, Hairong; Zhang, Xuanjun
Abstract: Copper enrichment in the brain is highly related to Alzheimer's disease (AD) pathogenesis, but in vivo tracing of Cu 2+ in the brain by imaging techniques is still a great challenge. In this work, we developed a series of activatable photoacoustic (PA) probes with low molecular weights (less than 438 Da), RPS1 –RPS4, which can specifically chelate with Cu 2+ to form radicals with turn‐on PA signals in the near‐infrared (NIR) region. Introducing the electron‐donating group N, N ‐dimethylaniline into the probe was found to significantly enhance the radical stability and PA intensity. The best probe in the series, RPS1, showed a fast response (within seconds) to Cu 2+ with high selectivity and a low PA detection limit of 90.9 nm . Owing to the low molecular weight and amphiphilic structure, RPS1 could effectively cross the blood–brain barrier (BBB) and thus allowed us, for the first time, to visualize Cu 2+ in vivo via PA imaging in the brains of AD mice. Abstract : Photoacoustic imaging of copper(II) in the brain : Small‐molecule probe RPS1 can selectively bind to Cu 2+ to form a radical with a turn‐on photoacoustic response in the near‐infrared region. RPS1 can effectively cross the blood–brain barrier and image copper(II) in the brain of a mouse suffering form Alzheimer's disease.